2009
DOI: 10.1371/journal.pone.0004687
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Profiling of Histone H3 Lysine 4 and Lysine 27 Trimethylation Reveals an Epigenetic Signature in Prostate Carcinogenesis

Abstract: BackgroundIncreasing evidence implicates the critical roles of epigenetic regulation in cancer. Very recent reports indicate that global gene silencing in cancer is associated with specific epigenetic modifications. However, the relationship between epigenetic switches and more dynamic patterns of gene activation and repression has remained largely unknown.Methodology/Principal FindingsGenome-wide profiling of the trimethylation of histone H3 lysine 4 (H3K4me3) and lysine 27 (H3K27me3) was performed using chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
115
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(127 citation statements)
references
References 42 publications
12
115
0
Order By: Relevance
“…Conversely, DNp63a increased protein (Figure 6a) and mRNA levels (twofold) of only integrin-b4, an effect that was not reverted by LNA205. Notably, miR-205 expression remained undetectable in DNp63a-expressing PC-3 cells (data not shown), thus confirming the strong epigenetic repression of the miRNA found in these cells 25 and showing that, in the absence of miR-205, p63 cannot enhance production of the whole laminin-332 complex. The retained ability of p63 to induce integrin-b4 may rely on a direct transcriptional activation, as reported by Carroll et al 26 In this context, integrin-b4 expression levels were the least affected by miR-205 silencing also in DNp63a-overexpressed RWPE-1 cells (Figure 6).…”
Section: Resultssupporting
confidence: 62%
“…Conversely, DNp63a increased protein (Figure 6a) and mRNA levels (twofold) of only integrin-b4, an effect that was not reverted by LNA205. Notably, miR-205 expression remained undetectable in DNp63a-expressing PC-3 cells (data not shown), thus confirming the strong epigenetic repression of the miRNA found in these cells 25 and showing that, in the absence of miR-205, p63 cannot enhance production of the whole laminin-332 complex. The retained ability of p63 to induce integrin-b4 may rely on a direct transcriptional activation, as reported by Carroll et al 26 In this context, integrin-b4 expression levels were the least affected by miR-205 silencing also in DNp63a-overexpressed RWPE-1 cells (Figure 6).…”
Section: Resultssupporting
confidence: 62%
“…It has been suggested that the tumorsuppressive function of miR-205 takes place through counteracting epithelial-to-mesenchymal transition and reducing cell migration and invasion in the human prostate (Gandellini et al, 2009;Majid et al, 2010). K27me3 modifications of the miR-205 locus was reported to occur in the PCa cell line PC3 (Ke et al, 2009) and in muscle-invasive bladder tumors and undifferentiated bladder cell lines (Wiklund et al, 2010). These findings, together with the early loss of miR-205 during PCa progression observed by us and others (Porkka et al, 2007;Ambs et al, 2008;Schaefer et al, 2010) present miR-205 as an attractive diagnostic marker for PCa disease.…”
Section: Discussionmentioning
confidence: 99%
“…A recent analysis of the methylation signature in PCa cell lines demonstrated that indeed histone methylation leads to the silencing of the entire mir-22l/222 cluster (Ke et al, 2009). Deregulation of several of the downregulated miRNAs identified in our prognostic profile has been demonstrated also in other human malignancies or diseases such as breast ) and colorectal cancer (Michael et al, 2003) for the mir-143/145 cluster; breast cancer (Zhao et al, 2008) and glioblastoma (Gillies and Lorimer, 2007) for the mir-221/222 cluster; and liver cancer (Datta et al, 2008) or cardiac hypertrophy (Care et al, 2007) for the mir-1/ 133 cluster.…”
Section: Discussionmentioning
confidence: 99%
“…Oligo Microarrays with SurePrint Technology (www.agilent.com) and hybridization data were extracted and formatted as published. 176 A multigene signature representing activation of the PI3K pathway was obtained from previously published expression data comparing cell lines transfected with PIK3CA (p119α) with GFP controls. The PI3Kinase signature included 495 genes that varied significantly in expression (Bonferroni-corrected 2-sided t-test P-value of 0.05) between control cells and the cells with PI3K pathway activity.…”
Section: Mrna Analysis -Gene Signaturementioning
confidence: 99%